Firm Competitiveness and the European Union Emissions Trading Scheme - Chan, Hei Sing (Elsevier, 2013)
The European Union Emissions Trading Scheme is the first international cap-and-trade program for CO2 and the largest carbon pricing regime in the world. A principle concern over the Emissions Trading Scheme is the potential impact on the competitiveness of industry. Using a panel of 5873 firms in 10 European countries during 2001–2009, this paper seeks to assess the impact of the carbon regulation on three variables through which the effects on firm competitiveness may manifest—unit material costs, employment and revenue. Our analysis focuses on three most polluting industries covered under the program-power, cement, and iron and steel. Empirical results indicate that the emissions trading program had different impacts across these three sectors. While no impacts are found on any of the three variables in cement and iron and steel industries, our analysis suggests a positive effect on both material costs and revenue in the power sector: the effect on material costs likely reflects the costs to comply with emissions constraints or other parallel renewable incentive programs while that on revenue may partly due to cost pass-through to consumers in a market less exposed to competition outside EU. Overall our findings do not substantiate concerns over carbon leakage, job loss and industry competitiveness at least during the study period.